Pengaruh Konten Instagram dan Electronic Word of Mouth (e-WOM) @indtravel Terhadap Minat Berkunjung ke Destinasi Wisata di Indonesia (Survey pada Followers Mancanegara @indtravel) - Rosetika Noviananda Pratiwi; Anita Maulina (JAMBIS : Jurnal Administrasi Bisnis, 2021)
Research Objectives: To analyze how much influence Instagram content and Electronic Word of Mouth have on visiting interest in Indonesian tourist destinations (survey on @indtravel international followers).In the era of globalization, the use of internet technology is increasingly being used in connection with meeting human needs. The use of Instagram Social Media is no exception as a medium that can foster interest in visiting various tourist destinations in Indonesia through content or through recommendations from other people conveyed in the media. The research method used in this research is descriptive quantitative research. The sample in this study, the international followers of the @indtravel Instagram account amounted to 100 respondents with probability sampling data taking by random sampling by Sugiyono (2017: 82). The types of data used in this study were obtained from primary data and secondary data. Data collection methods used, literature study and questionnaires. The data analysis technique used in this study is to test the validity, reliability, correlation coefficient and determination, multiple linear regression, and hypothesis testing. Research result. Partially there is an influence between Instagram content and electronic word of mouth on interest in visiting Indonesian tourist destinations (survey on @indtravel followers), this is known from the t test results obtained by tcount> ttable (2.162> 1.984) then H0 is rejected and H1 accepted. Meanwhile, according to the results of the F test simultaneously obtained the value of Fcount 14.925 with a value of 3.09. Thus, it is known that Fcount> Ftable means that together or variable Instagram content and electronic word of mouth (simultaneously) affect the interest in visiting Indonesian tourist destinations